2018
DOI: 10.18203/2319-2003.ijbcp20181633
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance pattern in intensive care unit of a tertiary care teaching hospital

Abstract: Background: Antimicrobials are a major class of drugs prescribed in Intensive Care Unit (ICU). Widespread use of empirical antibiotic therapy has facilitated the emergence of drug resistance, since empirical therapy is very often initiated at the outset, even before culture and sensitivity reports are available. The problem of drug resistance is on a rise, therefore, this study was planned to assess the drug resistance and sensitivity patterns of the blood isolates recovered from ICU.Methods: An observational-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
5
3
0
Order By: Relevance
“…Predominantly Gram-negative germs, found in our study, is consistent with the results of other researchers [19].…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…Predominantly Gram-negative germs, found in our study, is consistent with the results of other researchers [19].…”
Section: Resultssupporting
confidence: 94%
“…Consistent with our study, other investigators have reported also as the most common site of infection respiratory tract, urine and blood [3,19,[25][26][27].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…One-third of MRSA strains have been MDR, while both Coagulase-negative Staphylococci (CoNS) and MRSA showed resistance to penicillin in almost all patients, consistent also with other findings [22]. MRSA remains a major cause of healthcare-associated infections worldwide, with higher percentages in the southern and south-eastern parts of Europe [23].…”
Section: Resultssupporting
confidence: 73%